Soldier sailor : a novel - Kilroy, Claire, 1973- (Scribner, 2024)
"In her first novel for over a decade, Claire Kilroy takes readers deep into the early days of motherhood. Exploring the clash of fierce love for a new life with a seismic change in identity, Kilroy vividly explores the raw, tumultuous emotions of a new mother, as the narrator, Soldier's, marriage strains and she struggles with questions of equality, autonomy and creativity"--